Prior vaccination with rVSV-ZEBOV does not interfere with but improves efficacy of postexposure antibody treatment - Cross, Robert W.; Bornholdt, Zachary A.; Prasad, Abhishek N.; Geisbert, Joan B.; Borisevich, Viktoriya; Agans, Krystle N.; Deer, Daniel J.; Melody, Kevin; Fenton, Karla A.; Feldmann, Heinz; Sprecher, Armand; Zeitlin, Larry; et al. (Nature communications, 2020)
A replication-competent vesicular stomatitis virus vaccine expressing the Ebola virus (EBOV) glycoprotein (GP) (rVSV-ZEBOV) was successfully used during the 2013-16 EBOV epidemic. Additionally, chimeric and human monoclonal antibodies (mAb) against the EBOV GP have shown promise in animals and humans when administered therapeutically. Uncertainty exists regarding the efficacy of postexposure antibody treatments in the event of a known exposure of a recent rVSV-ZEBOV vaccinee. Here, we model a worst-case scenario using rhesus monkeys vaccinated or unvaccinated with the rVSV-ZEBOV vaccine. We demonstrate that animals challenged with a uniformly lethal dose of EBOV one day following vaccination, and then treated with the anti-EBOV GP mAb MIL77 starting 3 days postexposure show no evidence of clinical illness and survive challenge. In contrast, animals receiving only vaccination or only mAb-based therapy become ill, with decreased survival compared to animals vaccinated and subsequently treated with MIL77. These results suggest that rVSV-ZEBOV augments immunotherapy. During an ongoing Ebola virus outbreak, infection before onset of protective immunity from vaccination is a possible scenario. Here the authors show in non-human primates that vaccination shortly before treatment with a monoclonal antibody does not negatively affect effectiveness of the antibody therapy.